1975
DOI: 10.1002/jcp.1040860307
|View full text |Cite
|
Sign up to set email alerts
|

Development of excitability in embryonic chick skeletal muscle cells

Abstract: During embryonic and early postnatal development, the chick leg muscle cells undergo a series of changes in their electrical responses in the following sequence: passive response, plateau response, plateau plus spike response and spike response. This suggests that the electrogenetic mechanism of muscles matures during development; a mechanism producing the plateau may first be induced, and then that producing the spike. The plateau is sensitive to manganese or cobalt ions, while the spike to tetrodotoxin. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 21 publications
8
37
0
Order By: Relevance
“…A prolonged AP outlasting the stimulating pulse by several seconds has been described in embryonic chick myotubes in culture (18,24) and in situ (17). During development in situ this response appears before the fast AP and disappears after hatching (17 (25).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A prolonged AP outlasting the stimulating pulse by several seconds has been described in embryonic chick myotubes in culture (18,24) and in situ (17). During development in situ this response appears before the fast AP and disappears after hatching (17 (25).…”
Section: Discussionmentioning
confidence: 96%
“…The expression of these properties is autonomously regulated with no requirement for neuronal intervention. Although a rise in RP during differentiation of myotubes has been reported in culture (13)(14)(15) and in situ (16,17), low synchrony in differentiation produced large variability in electrical responses (17,18) and has hampered determination of the time of appearance and sequence of development of membrane excitability. Fischbach et al (13) The development of contractile activity is indicated by the early appearance of local twitches, which spread through the entire myotube upon maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They exist not only in fully differentiated cells but also already in oocytes (Okamoto et al, 1977) and in developing nerve and muscle cells (Spitzer, 1979). There are several reports that calcium channels are restricted to, or more prominent in, the less differentiated states of excitable cells such as skeletal cells (Kano, 1975;Kidokoro, 1973;Kidokoro, 1975) and nerve cells (Matsuda et al, 1978;Mori-Okamoto et al, 1983;Spitzer and Baccaglini, 1976). …”
Section: Electrophysiologymentioning
confidence: 99%
“…(Fukuda et al, 1976;Kano, 1975;Kano and Yamamoto, 1977). The involvement of a chloride component has also been shown in addition to the sodium and calcium component of the action potential, in particular in the long-lasting plateau phase of the action potential in these muscle cells (Fukuda et al, 1976).The availability of ATP in mammalian neurones is due to its wellknown role as a major energy carrier for cellular metabolism and has been reported to act as a fast transmitter in mammalian brain (Edwards and Gibb, 1993).…”
Section: Electrophysiologymentioning
confidence: 99%